Determinan Pemberian ASI Eksklusif - Agustini, Rahma Dewi; Wahyuni, Sri; Buheli, Kartin L.; Suherlin, Ika (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2021)
The World Health Organization (WHO) urges all mothers to exclusively breastfeed until their babies are 6 months old. Breastfeeding alone without complementary foods until the age of 6 months has enormous benefits for the development and growth of infants and strengthens the affection between mother and child. However, the amount of exclusive breastfeeding coverage is still low. Data from the Health Service in 2018 only 46% received exclusive breastfeeding even though the national exclusive breastfeeding target was 80%. This study aims to analyze the factors that influence exclusive breastfeeding in the working area of the Puskesmas which was carried out for one month. The crosssectional study design was conducted on 101 mothers with babies between 6 and 12 months who were selected by random sampling. The results of the chi-square analysis showed that there was an influence on age (p=0.001), parity (p=0.000), education (p=0.002), and knowledge (p=0.001). Conclusion: The percentage of failure to give exclusive breastfeeding is still high, with the factors of age, parity, education, and knowledge being very influential, so prevention efforts are needed that must be emphasized to mothers before giving birth.